2016
DOI: 10.1007/s12298-016-0381-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome differences between fiber-type and seed-type Cannabis sativa variety exposed to salinity

Abstract: The industrial hemp varieties 'Yunma 5' and 'Bamahuoma,' which demonstrate growth vigor and environmental adaptability, have been primarily cultivated in Yunnan and Guangxi, China, respectively, for fiber and seeds. The results of physiological measurements showed the phenotypic differences between the two varieties in response to salt stress. RNA-Seq analysis was first performed on leaves of both varieties sampled at four time intervals (0, 2, 4, 6 days) after treatment with salt (500 mM NaCl) We identified 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…It should, however, be noted that, despite the high NaCl concentration used, no visible signs of shock in the aerial parts of hemp plantlets could be noticed after the first application; while we cannot exclude the short-term (within hours) differential regulation of genes related to the osmotic component of salt shock, the aerial tissues appeared, phenotypically, as turgid as control plants, and no discernible discoloration could be noticed, either. Hemp is known to be a robust crop vs. exogenous constraints; nevertheless, different varieties showing varying susceptibility to salinity have already been studied in the literature [ 18 ]. Although further analyses are necessary to fully understand the susceptibility to salinity of the cultivar here studied, i.e., Santhica 27, we can claim that noticeable effects (growth arrest, loss of turgidity in the leaves) started to be clear only after 2 weeks of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should, however, be noted that, despite the high NaCl concentration used, no visible signs of shock in the aerial parts of hemp plantlets could be noticed after the first application; while we cannot exclude the short-term (within hours) differential regulation of genes related to the osmotic component of salt shock, the aerial tissues appeared, phenotypically, as turgid as control plants, and no discernible discoloration could be noticed, either. Hemp is known to be a robust crop vs. exogenous constraints; nevertheless, different varieties showing varying susceptibility to salinity have already been studied in the literature [ 18 ]. Although further analyses are necessary to fully understand the susceptibility to salinity of the cultivar here studied, i.e., Santhica 27, we can claim that noticeable effects (growth arrest, loss of turgidity in the leaves) started to be clear only after 2 weeks of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The primer sequences, amplification efficiencies and R 2 have either been previously published ( eTIF4E , TIP41 , F-BOX , RAN , PAL , CAD , 4CL , FLA1 - 3 - 6 - 8 - 10 , EXPA8 , CesA4 - 7 - 8 [ 19 , 23 ]), or are indicated in Table 1 . The identification numbers (IDs) of the genes actin depolymerizing factor 5 ADF5 , ethylene response factor ERF1 , auxin-responsive protein IAA11 , calcium-dependent lipid-binding family protein isoform 2 CALB2 , calcium-dependent lipid-binding family protein isoforms 4 CALB4-1 , -2 , -3 , heat shock protein 70 HSP70-1 and -2 , heat shock protein HSP81.4 , and gibberellin receptor 1b GIBB-REC , histidine kinase 4-like HK4 have been previously described [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. sativa is an annual herbaceous crop of increasing economic importance for a multitude of uses: hemp-type cultivars are a significant source of bast and woody fibers and drug-type cultivars produce a trove of secondary metabolites (namely Δ 9 -tetrahydrocannabinolic acid ~ THCA and cannabidiolic acid ~ CBDA) which are of significant medicinal value ( Gonçalves et al, 2019 ). Hemp-type cultivars of C. sativa [those which produce < 0.3% THC according to Small et al (1975) ] demonstrate several mechanisms to enhance tolerance to NaCl ( Liu et al, 2016 ; Guerriero et al, 2017 ). Hemp has shown some ability to tolerate NaCl in trials involving seed germination (> 70% germinating in 150 mM NaCl) ( Hu et al, 2018 ) and seedling development (4.4% greater chlorophyll content at 100 mM NaCl compared to the control) ( Hu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the decrease in physiological parameters for plants grown in hydroponic solution, it is suggested that such mechanisms observed in hemp may not occur to the same extent in drug-type cultivars; however, further research is needed to quantify the production of radicals and stress related proteins to verify this. Furthermore, future research should involve multiple cultivars, to clarify if drug-type C. sativa cultivars have a cultivar-dependent response to NaCl as prominently shown in hemp-type cultivars (Liu et al, 2016).…”
mentioning
confidence: 99%